Agronomic biofortification increases concentrations of zinc and storage proteins in common bean (Phaseolus vulgaris L.) grains - Kachinski, Wagner Deckij; Ávila, Fabrício William; dos Reis, André Rodrigues [UNESP]; Muller, Marcelo Marques Lopes; Mendes, Marcelo Cruz; Petranski, Poliana Horst (Elsevier, 2022)
Zinc (Zn) is an essential element for plants and mammals and its deficiency affects billions of people worldwide. This study aimed to evaluate the effects of soil Zn fertilization and foliar Zn sprays in different phenological stages of the plant on the grain nutritional quality of common bean (Phaseolus vulgaris L.). Field experiments were carried out in two consecutive harvest years under no-till system in an Oxisol. Two commercial common bean cultivars were used: BRS Esteio (black bean) and IPR Campos Gerais (Carioca bean). Total concentration of Zn, amino acids, sucrose, total sugars and storage proteins (albumin, globulin, glutelin and prolamin) in grains were evaluated. The cultivar BRS Esteio exhibited higher grain enrichment with Zn than the cultivar IPR Campos Gerais, showing genotypic variation. Single foliar Zn spray of 600 g ha−1 at the initial grain filling stage was shown to be the best way to improve the grain Zn concentration, without affecting grain yield. Foliar Zn spray at the final stage of grain filling favored the increase of Zn concentration in the pods over the Zn concentration in the grains. Agronomic biofortification of bean grains with Zn was more efficient with foliar Zn spraying than with the soil Zn fertilization, however, the soil Zn application favored the increase of concentrations of total amino acids and storage proteins (albumin, globulin and glutelin) in the grains. Agronomic biofortification proved to be efficient in increasing concentrations of Zn and storage proteins in common bean grains.
Keywords: Biofortified foods; Micronutrient; Nutritional safety; Phaseolus vulgaris L.; Plant nutrition